Microvascular Changes in the Choriocapillaris of Diabetic Patients Without Retinopathy Investigated by Swept-Source OCT Angiography - Dai, Yining (Invest Ophthalmol Vis Sci, 2020)
PURPOSE: To investigate the microvascular changes in macular retina and choriocapillaris (CC) in diabetic eyes without retinopathy using swept-source optical coherence tomography angiography (SS-OCTA). METHODS: A commercial SS-OCTA system was used to collect 6 × 6-mm macular scans from patients. Three depth-resolved retinal slabs and a CC slab were segmented by a validated semiautomated algorithm. Retinal vessel area density, vessel skeleton density, and nonperfusion area were calculated on segmented retinal slabs. Foveal avascular zone was automatically measured based on en face image of the whole retinal layer. For CC quantification, the percentage of flow deficits (FD%) and the flow deficit (FD) sizes were measured.  RESULTS: Sixteen eyes from 16 diabetic patients without clinically detectable retinopathy and 16 eyes from 16 age-matched nondiabetic controls were included. There was no significant difference between the two groups in all retinal vessel quantitative parameters (all P > 0.05). However, the mean FD% and mean FD sizes were significantly increased in CC in the central 1.0-mm disk (P = 0.011 and P = 0.017, respectively), the central 1.5-mm rim (P = 0.003 and P = 0.009, respectively), the central 2.5-mm rim (P = 0.018 and P = 0.020, respectively), and the entire 5.0-mm disk (P = 0.009 and P = 0.008, respectively) in diabetic eyes compared with controls. CONCLUSIONS: CC perfusion in the macula is decreased in diabetic patients without retinopathy as compared to age-matched normal controls. Decreased CC perfusion in the macula may be an early indicator of otherwise clinically undetectable diabetic vasculopathy.